2020
DOI: 10.7759/cureus.9920
|View full text |Cite
|
Sign up to set email alerts
|

Romiplostim and Eltrombopag in Immune Thrombocytopenia as a Second-Line Treatment

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by platelet count less than 100×10 9 /L and an increased risk of bleeding. The risk of bleeding increases in proportion with the degree of thrombocytopenia. Although several medications are used for primary thrombocytopenia treatment, refractoriness remains a concern. Romiplostim and eltrombopag, two relatively new drugs, have been shown to be successful in ITP treatment after standard treatment failure. The current gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Romiplostim or eltrombopag have been investigated in several randomized controlled trials involving adult and pediatric ITP patients [7][8][9], and meta-analysis reports show that TPO receptor agonists with ITP patients were an effective secondline treatment option for primary ITP patients, in whom at least one previous therapy has failed [10]. Among patients treated with romiplostim, an average of 75% showed a significant response in platelet counts, whereas 69% of patients responded with eltrombopag [11]. An initial response to TPO-RA commonly appears within 1 to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Romiplostim or eltrombopag have been investigated in several randomized controlled trials involving adult and pediatric ITP patients [7][8][9], and meta-analysis reports show that TPO receptor agonists with ITP patients were an effective secondline treatment option for primary ITP patients, in whom at least one previous therapy has failed [10]. Among patients treated with romiplostim, an average of 75% showed a significant response in platelet counts, whereas 69% of patients responded with eltrombopag [11]. An initial response to TPO-RA commonly appears within 1 to 2 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…An initial response to TPO-RA commonly appears within 1 to 2 weeks. If one TPO-RA agent is ineffective, switching to the other leads to a platelet response in up to 50% of patients [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eltrombopag is well tolerated and has a good safety profile in adults. 12 Upon literature review, there are no studies or case reports that document the association between Eltrombopag and regression of IBD. Despite there is no clear pathogenesis, but the immunomodulatory effect of Eltrombopag could decrease the inflammatory response of IBD.…”
Section: Discussionmentioning
confidence: 99%
“…It can effectively increase platelet counts and reduce bleeding events in patients with chronic ITP, with an overall response rate of 60% to 80%. Eltrombopag is well tolerated and has a good safety profile in adults 12 …”
Section: Discussionmentioning
confidence: 99%
“…Response rates and the onset of action with romiplostim are similar to eltrombopag (Table 2). The sustained remission after stopping romiplostim is observed in 10-30% of patients (Cooper et al, 2019;Shirasugi et al, 2011;Bidika et al, 2020;Puravilai et al, 2020). A recent study from the United States has shown an overall response rate of more than 90% with romiplostim, which inversely correlated with the duration of ITP (Kuter et al, 2013).…”
Section: Romiplostimmentioning
confidence: 99%